ctDNA Detection Based on DNA Clutch Probes and Strand Exchange Mechanism - Chang, Huan; Zhang, Yiyi; Yang, Fan; Wang, Changtao; Dong, Haifeng (Frontiers in Chemistry, 2018)
Circulating tumor DNA (ctDNA), originating directly from the tumor or circulating tumor cells, may reflect the entire tumor genom and has gained considerable attention for its potential clinical diagnosis and prognosis throughout the treatment regimen. However, the reliable and robust ctDNA detection remains a key challenge. Here, this work designs a pair of DNA clutch separation probes and an ideal discrimination probes based on toehold-mediated strand displacement reaction to specifically recognize ctDNA. First, the ctDNAs were denatured to form ssDNAs, the pair of DNA clutch separation probes (one of which modified onto the magnetic nanoparticles (MNPs)) are used to recognize and hybridize with the complemental chains and prevent reassociation of denatured ssDNAs. The complemental chains are removed in magnetic field and left the wild and mutant ssDNA chains in the supernatant. Then, the toehold-mediated strand displacement reaction specificity recognizes the target mutant sequence to ensure only the mutated strands to be detection. The proposed assay exhibited good sensitivity and selectivity without any signal amplification. The proposed assay displayed a linear rang from 2-100 nM with a limit of detection (LOD) of 0.85 nM, and it was useful for ctDNA biomedical analysis and clinic theranostic.